Combination of Wogonin and Artesunate Exhibits Synergistic anti-Hepatocellular Carcinoma Effect by Increasing DNA-Damage-Inducible Alpha, Tumor Necrosis Factor α and Tumor Necrosis Factor Receptor-Associated Factor 3-mediated Apoptosis - Chen, Minting; Wu, Hsin Ling; Wong, Tsz Sin; Chen, Baisen; Gong, Rui-Hong; Wong, Hoi Leong Xavier; Xiao, Haitao; Bian, Zhaoxiang; Kwan, Hiu Yee (Frontiers in Pharmacology, 2021)
Hepatocellular carcinoma (HCC) is difficult to treat, and is the second leading cause of cancer-related death worldwide. This study aimed to examine whether combination of wogonin and artesunate exhibits synergistic anti-HCC effect. Our data show that the combination treatment exhibits synergistic effect in reducing HCC cell viability by increasing apoptosis as indicated by the elevated cleavage of caspase 8, 3 and PARP. Interestingly, PCR array and the subsequent studies indicate that the combination treatment significantly increases the expression of DNA-damage-inducible, alpha (GADD45A), tumor necrosis factor (TNFα) and TNF receptor-associated factor 3 (TRAF3). Knockdown of GADD45A, TNF α or TRAF3 abolishes the combination treatment-enhanced apoptosis and the synergistic effect in reducing HCC cell viability. In the HCC-bearing xenograft mouse models, although the combination treatment increases the activity of NFκB in the tumor tissues, it exhibits a more potent anti-HCC effect than the mono-treatment, which may due to the enhanced apoptosis as indicated by the increased expression of GADD45A, TNFα, TRAF3 and apoptotic markers. Our study clearly demonstrates the combination of artesunate and wogonin exhibits synergistic anti-HCC effect, and support the further development of this combination as alternative therapeutics for HCC management.